2011
DOI: 10.1097/01.yic.0000405843.25701.ca
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging sex differences in emotional memory in schizophrenia patients

Abstract: DSM-IV criteria) were not included. -Scanning Procedures: Patients and controls were scanned with a head coil in a 1.5 T magnet, using a whole-brain echo plannar DTI sequence with 25 gradient directions and b = 900 mm/s2, 128 Â 128 matrix and 25 cm FOV. -Data Analysis: Image Processing and Statistical Analyses: The original DTI data were transferred to a PC based Linux workstation, anonymized and converted to NIFTI format, and then processed to obtain the fractional anisotropy (FA) maps after eddy currents cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As in schizophrenic patients, it is common to find a reduced global activation in response to the unpleasant valence images, compared to neutral ones, during basic emotional tasks per se and during emotional memory tasks as well ( Schneider et al, 1998 ; Takahashi et al, 2004 ; Lakis et al, 2011a ). For instance, Lakis et al (2011b) showed that during a task of unpleasant image recognition, the cerebral activation was greater in the temporal and middle temporal gyrus, the precuneus, the cerebellum, the prefrontal cortex (orbitofrontal, upper and middle) and the cingulate gyrus in control individuals, while in schizophrenia patients exhibited significant activations only in the middle temporal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…As in schizophrenic patients, it is common to find a reduced global activation in response to the unpleasant valence images, compared to neutral ones, during basic emotional tasks per se and during emotional memory tasks as well ( Schneider et al, 1998 ; Takahashi et al, 2004 ; Lakis et al, 2011a ). For instance, Lakis et al (2011b) showed that during a task of unpleasant image recognition, the cerebral activation was greater in the temporal and middle temporal gyrus, the precuneus, the cerebellum, the prefrontal cortex (orbitofrontal, upper and middle) and the cingulate gyrus in control individuals, while in schizophrenia patients exhibited significant activations only in the middle temporal cortex.…”
Section: Introductionmentioning
confidence: 99%